The Rise of Private Foundations as Owners of Swedish Industry: The Role of Tax Incentives 1862–2018 - Dan Johansson; Mikael Stenkula; Niklas Wykman (Örebro University School of Business, 2018)
The tax system has at times favoured firm control through private foundations, which has been argued to inhibit high-impact entrepreneurship and economic growth. However, research has been hampered due to a lack of systematic historical tax data. The purpose of this study is threefold. First, we describe the evolution of tax rules for private foundations in Sweden between 1862 and 2018. Second, we calculate the marginal effective tax rate on capital income. Third, we examine the incentives to use private foundations as a means for corporate control by comparing the taxation of private foundations and of high-impact entrepreneurs. Tax incentives help explain why economically significant private foundations were founded between World War I and the 1960s.
Keywords: H20; K34; L26; N44; 330; family firms; foundations; high-impact entrepreneurship; owner; taxation